Pengaruh Persepsi Mahasiswa Tentang Kompensasi Finansial dan Lingkungan Kerja terhadap Minat Memilih Profesi Guru pada Mahasiswa Pendidikan Ekonomi - Jean Elikal Marna; Junia Latiffa (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2021)
This study aims to find out 1) Influence of Student Perception on Financial Compensation and Work Environment On Interest in Choosing Teacher Profession In Economic Education Students 2) Influence of Student Perception On Financial Compensation On Interest in Choosing Teacher Profession In Economic Education Students and 3) Influence of Student Perception About Work Environment On Interest in Choosing Teacher Profession In Economic Education Students. The population in this study was students of Economic Education Faculty of Economics, Universitas Negeri Padang and the number of selected samples as many as 119 students. This type of research is descriptive associative research. The sampling technique used in this study is probability sampling by using proportional stratified random sampling. Data analysis using descriptive analysis, analysis requirement test, multiple regression, F test, determinant coefesien and t test. The results showed that 1) Students' Perception of Financial Compensation and Work Environment  had a significant effect on the Interest in Choosing a Teacher Profession. 2) Student Perception of Financial Compensation has a significant effect on the Interest in Choosing a Teacher Profession. 3) Student Perception of The Work Environment has a significant effect on the Interest in Choosing a Teacher Profession.